Identification of Polyphenolic Components in Unripe Banana Pulp and Their Inhibitory Effects on α-Amylase and α-Glucosidase - WANG Qian, WANG Juan, FU Jinfeng, SHENG Ou (Shipin Kexue, 2024)
The composition of phenolics extracted from unripe banana flesh was identified using ultra-high performance liquid chromatography coupled with Q-Exactive Orbitrap mass spectrometry (UPLC-Q-Exactive Orbitrap-MS), and the inhibitory effects of banana polyphenols on α-amylase and α-glucosidase were estimated in vitro. In total, 28 compounds were identified, including 21 polyphenols such as esculetin, hyperoside, and kaempferol-3-O-glucoside, 2 organic acids, 3 ellagitannin metabolites, vanillin and coumarin. In addition, dimethyl ellagic acid and urolithin A were the major chromatographic peaks. Banana polyphenols exhibited excellent inhibitory effects on both α-amylase and α-glucosidase with half maximal inhibitory concentration (IC50) of 0.53 mg/mL and 35.76 µg/mL, respectively. At concentrations of 1.0 mg/mL and 160 µg/mL, the inhibition rates of α-amylase activity and α-glucosidase were (76.25 ± 3.79)% and (92.54 ± 0.69)%, respectively. Therefore, polyphenols may be one of the active ingredients contributing to the anti-hypoglycemic effect of unripe bananas.